2008
DOI: 10.1007/s10661-008-0367-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of groundwater metal loads from bedrock fractures on water quality of a mountain stream

Abstract: Acid mine drainage and metal loads from hardrock mines to surface waters is a significant problem in the western USA and many parts of the world. Mines often occur in mountain environments with fractured bedrock aquifers that serve as pathways for metals transport to streams. This study evaluates impacts from current and potential future groundwater metal (Cd, Cu, and Zn) loads from fractures underlying the Gilt Edge Mine, South Dakota, on concentrations in Strawberry Creek using existing flow and water qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…One possible mechanism for release of (filterable fraction) metals from the mine waste is the rewetting of evaporative salts formed on, and within, the mine wastes during dry antecedent conditions, 14 but further investigation would be needed to Groundwater discharge under high flow conditions is commonly observed in mining-impacted catchments 12,14,16 and can represent an important diffuse source of metals, particularly in areas where substantial fracturing of bedrock occurs. 18,35 As the Coledale Beck flow rate increases during rainfall events an increasing discrepancy occurs between the sum of all measurable upstream flows and the Coledale Beck downstream of the mine site (Figure S7), indicating the presence of additional, unmeasured, flows. These are likely shallow subsurface flows and surface runoff.…”
Section: ■ Discussionmentioning
confidence: 99%
“…One possible mechanism for release of (filterable fraction) metals from the mine waste is the rewetting of evaporative salts formed on, and within, the mine wastes during dry antecedent conditions, 14 but further investigation would be needed to Groundwater discharge under high flow conditions is commonly observed in mining-impacted catchments 12,14,16 and can represent an important diffuse source of metals, particularly in areas where substantial fracturing of bedrock occurs. 18,35 As the Coledale Beck flow rate increases during rainfall events an increasing discrepancy occurs between the sum of all measurable upstream flows and the Coledale Beck downstream of the mine site (Figure S7), indicating the presence of additional, unmeasured, flows. These are likely shallow subsurface flows and surface runoff.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Detailed examination of the concentration changes revealed that trace elements loadings might come from: the gold processing facilities, AMD from mine waste dumps, and other industrial activities. In addition, polluted ground water (Caruso and Dawson 2009) and release or resuspension of elements from contaminated sediment (Beltran et al 2010) as a response to early diagenesis can also influence trace element concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Acid rock drainage (ARD) is a major pollution problem throughout the world, adversely affecting both surface and ground waters (Gerhardt 1993, Gray 1996, Caruso and Dawson 2009.…”
Section: Problem Statementmentioning
confidence: 99%